Про тривимірну задачу лінеаризованої магнітострикції феритів з феромагнітним резонансом - Шульга, М.О.; Левченко, В.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The full system of three-dimensional equations of linearized magnetostriction for ferrites in view of a ferromagnetic resonance is transformed to a system of eight equations of the operational Hamilton type for rather definitely chosen initial variables.